1985
DOI: 10.1177/002193478501600205
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Structure of the Ghetto and the Criminal Commute

Abstract: The diversity of the urban landscape continues to be part of our understanding of urban social problems in America. Urbanization and its attendant characteristics have long been sacrosanct, and our understanding of the geographical character of crime relies in part on analyzing the disparate elements of the urban matrix. Social ecologists agree that urban crime is a product of the interaction of the social, cultural, and economic factors associated with urban areas. In this way, crime has been linked inextrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…These well-documented features of U.S. cities, including Chicago (e.g., Johnston, Poulson, and Forrest, 2003;Massey, 1990;Wilson, 1987), are likely to restrain the mobility of its population, including offenders, and can be considered as a "social barrier" (Rengert, 2004). Pettiway (1982Pettiway ( , 1985 studied the mobility of burglars and robbers in Milwaukee and distinguished three types of areas on the basis of the racial composition of the population: the black ghetto area, the white non-ghetto area, and an interstitial area around the ghetto (where the composition was more racially mixed). He observed that those who lived in the black ghetto would overwhelmingly offend there, whereas those who did not offended outside the ghetto.…”
Section: Racial and Ethnic Barriersmentioning
confidence: 99%
“…These well-documented features of U.S. cities, including Chicago (e.g., Johnston, Poulson, and Forrest, 2003;Massey, 1990;Wilson, 1987), are likely to restrain the mobility of its population, including offenders, and can be considered as a "social barrier" (Rengert, 2004). Pettiway (1982Pettiway ( , 1985 studied the mobility of burglars and robbers in Milwaukee and distinguished three types of areas on the basis of the racial composition of the population: the black ghetto area, the white non-ghetto area, and an interstitial area around the ghetto (where the composition was more racially mixed). He observed that those who lived in the black ghetto would overwhelmingly offend there, whereas those who did not offended outside the ghetto.…”
Section: Racial and Ethnic Barriersmentioning
confidence: 99%
“…These “hustles” arise through a combination of planning and spontaneity that is driven by both addiction and economics, and actively shaped by multiple “elements in the urban matrix” (Pettiway, 1985). In his words,

When I wake up, I usually try to have that [money for heroin] the night before.

…”
Section: Findings: Heroin Circulationsmentioning
confidence: 99%
“…The intensity of ghettoization (Zukin 1998; Chaddha & Wilson, 2008; Gans, 2008) may be one important corollary of the entrenchment and operation of such markets. Both criminal behavior and the perpetuation of racial segregation may be conceived as dynamic interactions of individuals with these already segregated environments (Pettiway, 1982, 1985; Yin, 2009). Neighborhood disadvantage and disorder, as research has repeatedly shown, generate effects that worsen the mental health of residents, making substance abuse more likely (Ensminger, Anthony & McCord, 1997; Nikelly, 2001; Boardman et al, 2001).…”
Section: Conclusion and Future Directions For Researchmentioning
confidence: 99%
See 2 more Smart Citations